IMPACT OF PHYTOESTROGENS ON ENDOCRINE GLANDS OF CT OF PHYTOESTROGENS ON ENDOCRINE GLANDS OF ALBINO RATS I. PITUITARY - EMMA R. SERAPHIM; M. P. SINHA (The Bioscan, 2010)
Studies have been conducted to determine the impact of estrogenic activities of ethanolic extract of seeds of Citrus medica on pituitary gland of albino rats. Histological preparations by differential staining pituitary gland of extract treated sexually immature and ovariectomised female albino rats are observed under light microscope on the basis of the tinctorial response of different cells. The increased uterine weight and highly developed uterine glands proved the estrogenic activity of the ethanolic extract of the seeds of Citrus medica. Pars distalis of pituitary gland of control rats showed presence of significant number of STH cells and moderate number of LTH cells (acidophils). A number of gonadotrophs were observed. Thyrotrophs were scattered throughout the pars distalis and were found mainly present towards the periphery while the pars distalis of ethanolic extract of treated rats showed insignificant changes in the number of acidophils STH and LTH. Thyrotrophs were granulated and scattered throughout the pars distalis. The numbers of gonadotroph FSH were significantly increased.